2021
DOI: 10.1177/09612033211005067
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled bone remodeling is characteristic of bone damage in premenopausal women with new-onset systemic lupus erythematosus

Abstract: Objective To investigate the mechanism underlying systemic lupus erythematosus (SLE)-related bone loss by evaluating the bone mineral density (BMD) and bone turnover markers (BTMs) in premenopausal patients with new-onset SLE without any treatment. Methods BMD and BTMs of 106 premenopausal patients with new-onset SLE and 64 gender-, age- and body mass index (BMI)-matched healthy controls were analyzed. BMD was determined using dual energy X-ray absorptiometry (DXA). Serum BTMs were measured. Results Hip and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Osteopenia occurs already in pre-menopausal SLE patients but worsens significantly after menopause. 4 Additionally, a recent publication showed lower BMD in pre-menopausal SLE patients compared with healthy controls, 5 further highlighting the risk for osteoporosis development in these patients. SLE patients also have an almost 3-fold increased risk of vertebral fractures compared with age-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…Osteopenia occurs already in pre-menopausal SLE patients but worsens significantly after menopause. 4 Additionally, a recent publication showed lower BMD in pre-menopausal SLE patients compared with healthy controls, 5 further highlighting the risk for osteoporosis development in these patients. SLE patients also have an almost 3-fold increased risk of vertebral fractures compared with age-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…The number of risk factors can increase the chances of developing osteoporosis. Patients with the following medical problems have a higher risk for developing osteoporosis: cancer, in particular breast cancer [98,99], rheumatoid disorders such as rheumatoid arthritis [100,101] or systemic lupus erythematosus [102], chronic kidney or liver diseases [103,104], diabetes mellitus [105,106], Parkinson's disease [107], and multiple myeloma [108]. Eating disorders such as anorexia [109] nervosa, poor nutrition, or dietary factors such as a low calcium intake [110] can also cause osteoporosis, as calcium plays an important role in the development of bone.…”
Section: Changes In the Bone-remodeling Process In Osteoporosismentioning
confidence: 99%
“…Beyond that, autoimmune disease activity, independent of steroid use, can predispose patients to bone-density loss. A recent study of new-onset SLE patients (prior to use of glucocorticoids) found that premenopausal women exhibited significantly decreased BMD in hip and lumbar spine when compared with controls [3]. Prevention and management of osteoporosis within the context of autoimmune disease is an important part of the comprehensive care of chronic diseases managed by rheumatologists.…”
Section: Introductionmentioning
confidence: 99%